The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s11671-017-2002-3
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel Synthesis, Photo- and Electrocatalytic Properties of Mesoporous TiO2 Modified with Transition Metal Ions

Abstract: Mesoporous nanosized titania films modified with Co2+, Ni2+, Mn3+, and Cu2+ ions have been produced by templated sol-gel method and characterized by optical spectroscopy, X-ray diffraction (XRD), and Brunauer, Emmett, and Teller (BET) surface area measurement. Band gap energy and the position of flat band potentials were estimated by photoelectrochemical measurements. The films doped with transition metals possessed higher photocurrent quantum yield, as well as photo- and electrochemical activity compared to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Furthermore, the spectrum of the TO-Ni-05 sample showed an absorption peak with a maximum at approximately 725 nm, the intensity of which strongly depended on nickel concentration (Figure S5, Supplementary Materials). This peak has previously been reported in the literature and was attributed to Ni 2+ ions in the octahedral coordination [48]. With regard to Zn-doped TiO2(B), its absorption edge also moved slightly toward longer wavelengths (i.e., red-shifted) as compared to the undoped sample.…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, the spectrum of the TO-Ni-05 sample showed an absorption peak with a maximum at approximately 725 nm, the intensity of which strongly depended on nickel concentration (Figure S5, Supplementary Materials). This peak has previously been reported in the literature and was attributed to Ni 2+ ions in the octahedral coordination [48]. With regard to Zn-doped TiO2(B), its absorption edge also moved slightly toward longer wavelengths (i.e., red-shifted) as compared to the undoped sample.…”
Section: Resultssupporting
confidence: 76%
“…3, образцы № 1 -№ 5) определены их фотоэлектрохимические характеристики: потенциал плоских зон (Е пз ) и ширина запрещенной зоны (Е g ) для непрямых фотопереходов в запрещенной зоне TiO 2 . Значение потенциала плоских зон Е пз определяли из зависимостей фототока (І ф ) от потенциала Е. Значение Е пз позволяет оценить изменение положения дна зоны проводимости и энергию электронов, при участии которых протекают процессы восстановления, в том числе процесс электровосстановления кислорода [44]. Для определения ширины запрещенной зоны Е g спектральные зависимости квантового выхода фотоэлектрохимического тока перестраивались в координатах (hν×η) 0,5 ~ hν для непрямых разрешенных переходов в TiO 2 , где ηквантовый выход; hνэнергия кванта света.…”
Section: фоточувствительность Tio 2 -наноструктур и композитов Tio 2 -001%auunclassified
“…Titanium oxide (TiO 2 ) was the most promising photocatalyst because of its environmental friendliness, low cost, and stable properties. Studies have been reported to improve the performance of TiO 2 by combining it with other materials, such as doping cations (rare earth and transition metals) [ 26 , 27 ] or anions (halogen, sulfur, carbon, and nitrogen) [ 28 ], since high photoelectron-hole pair recombination rate reduced the efficiency of TiO 2 . Studies about TiO 2 with chlorophyll have been reported to broaden TiO 2 absorbance wavelength to visible light and reduce photoelectron-hole pair recombination rate [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%